1980
DOI: 10.1177/030006058000800410
|View full text |Cite
|
Sign up to set email alerts
|

Post-Marketing Surveillance of Euhypnos® (Temazepam): A New Hypnotic

Abstract: A post-marketing surveillance study of Euhypnos (temazepam), a new short-acting benzodiazepine hypnotic. A total of 12,350 patients requiring a sleep inducer were treated for up to 3 months with doses of 10-30 mg at night. After 2 weeks 80% of First Reports (FRs) rated Euhypnos effective and at 3 months this had risen to 92% of 3062 Second Reports (SRs). Hangover was reported in 7% of FRs and 2% of SRs but in general the drug was well tolerated with adverse reactions consisting mainly of morning nausea, headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In general, the design of post-marketing surveillance studies allows for adequate de tection of the rate of adverse reactions [36]. For hypnotics, however, the few existing post-marketing studies have provided only a global side effect rate [38][39][40], It also seems more likely that the reports of adverse drug reactions submitted to the SRS of the FDA include more unexpected side effects than reports collected in post-marketing studies. This is mainly due to the design of the sur veillance studies which may allow expected or augmented drug effects to 'mask' the un expected or bizzare side effects.…”
Section: Consistency O F Findings With Those O F Laboratory and Clinimentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the design of post-marketing surveillance studies allows for adequate de tection of the rate of adverse reactions [36]. For hypnotics, however, the few existing post-marketing studies have provided only a global side effect rate [38][39][40], It also seems more likely that the reports of adverse drug reactions submitted to the SRS of the FDA include more unexpected side effects than reports collected in post-marketing studies. This is mainly due to the design of the sur veillance studies which may allow expected or augmented drug effects to 'mask' the un expected or bizzare side effects.…”
Section: Consistency O F Findings With Those O F Laboratory and Clinimentioning
confidence: 99%
“…therefore, expected side ef fects rather than any unexpected reactions [36], Furthermore, in pre-marketing clinical trials of hypnotic drugs, in order to obtain a large sample size, data originating from many studies with different methodologies have been combined and presented under the assumption that they were collected in a uniform manner [37J. Also, the few post marketing surveillance studies available for hypnotic drugs do have very large sample sizes, but have reported only global side effect rates [38][39][40],…”
mentioning
confidence: 99%